1996
DOI: 10.1136/bmj.312.7042.1321
|View full text |Cite|
|
Sign up to set email alerts
|

Cost effectiveness of screening for and eradication of Helicobacter pylori in management of dyspeptic patients under 45 years of age

Abstract: Objective-To assess the cost effectiveness of screening for and eradicating Helicobacter pylori in patients under 45 years of age presenting with dyspepsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
0
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(92 citation statements)
references
References 16 publications
1
89
0
2
Order By: Relevance
“…A decision-analytic model comparing empirical anti-secretory therapy with H. pylori screening found that it would take 5-18 years for savings to accrue if the latter strategy did not influence patient behaviour. 20 However, some recent evidence suggests that knowledge of H. pylori status can reassure patients and may be a cost-effective strategy. 21 Test-and-treat PUD is cured by H. pylori eradication, and there are now safe and relatively inexpensive regimens that effectively treat this organism.…”
Section: Screening For H Pylorimentioning
confidence: 99%
See 2 more Smart Citations
“…A decision-analytic model comparing empirical anti-secretory therapy with H. pylori screening found that it would take 5-18 years for savings to accrue if the latter strategy did not influence patient behaviour. 20 However, some recent evidence suggests that knowledge of H. pylori status can reassure patients and may be a cost-effective strategy. 21 Test-and-treat PUD is cured by H. pylori eradication, and there are now safe and relatively inexpensive regimens that effectively treat this organism.…”
Section: Screening For H Pylorimentioning
confidence: 99%
“…(i) benefits are usually limited to a 'avoided costs'and assumptions about effectiveness of different treatments are limited (ii) case-mix is poorly considered; most studies are limited to effects engendered by H. pylori eradication on recurrent PUD alone (iii) modelling approaches are usually limited to one or two strategies with no analysis of different prescribing choices (iv) most studies exclude any high-cost serious outcomes, such as bleeding ulcers or cancers (v) international comparisons, especially with those high USA healthcare costs, are difficult and potentially misleading (vi) most studies are limited to 1-year fixed period; there were only two Markov models 20,229 and no simulation approaches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that a strategy of screening dyspeptic patients under 45 prior to endoscopy may be worthwhile, 39 with eradication in those with proven ulcers ('test and scope'). Strategies of screening and eradication for H. pylori in dyspepsia ('test and treat') have been evaluated, and may be more costeffective, 40,41 but the issue of screening the larger asymptomatic population has not been studied in the UK. The case for screening for H. pylori rests on the public health burden of gastric cancer and peptic ulcer disease, and on the availability of a valid screening test for H. pylori and of effective eradication therapy.…”
mentioning
confidence: 99%
“…A British group have used a simple Markov model to simulate long-term costs and outcomes associated with the treatment of recurrent peptic ulcer over a 10-year period. 31 The authors compared conventional treatment with cimetidine (intermittent therapy, with maintenance treatment after second recurrence or delayed healing), with H. pylori eradication therapy (two attempts, with routine 13C-urea breath testing). Only direct medical costs were estimated, and ulcer complications were not considered.…”
Section: Sek) Costs Of Treating Drug Side Effectsmentioning
confidence: 99%